Impact of ceria over WO3–ZrO2 supported Ni catalyst towards hydrogen production through dry reforming of methane. (16th July 2021) - Patel, Rutu; Al-Fatesh, Ahmed S.; Fakeeha, Anis H.; Arafat, Yasir; Kasim, Samsudeen O.; Ibrahim, Ahmed A.; Al-Zahrani, Salma A.; Abasaeed, Ahmed E.; Srivastava, Vijay Kumar; Kumar, Rawesh
Abstract: ZrO2 supported Nickel catalyst, 9 wt%WO3 -91 wt%ZrO2 supported Nickel catalyst and ceria promoted 9 wt%WO3 -91 wt%ZrO2 supported Nickel catalyst (5NixCe/WZr catalyst) is synthesized via wet impregnation and characterized by XRD, UV–vis, CO2 -TPD, H2 TPR-CO2 TPD-H2 TPR cycle, TPH, TPH followed by O2 -TPO and CO2 -TPD followed by O2 -TPO. Due to limitation in surface re-oxidizing capability and shading of catalytic active sites by thermally stable carbonates; catalytic activity of unpromoted catalyst system is less. 5NixCe/WZr catalyst has extended CH4 decomposition sites, additional basic sites (during the reaction) for CO2 adsorption and excellent redox accompany (Ce +4 /Ce +3, W+ 6 /W +4 ) for carbon oxidation and re-oxidizing capability of surface up to the pristine level. 2.5 wt% Ceria promotional addition is resulted into 78% H2 yield constantly up to 420 min TOS. The carbon deposit over ceria promoted system (up to 2.5 wt%) is amorphous type, more easily/moderately reducible, oxidizable and removable. Highlights: 2.5%Ceria promoted WO3 –ZrO2 supported Ni carries extended CH4 decomposition sites. Additional redox accompany (Ce +4 /Ce +3, W +6 /W +4 ) gear up carbon deposit oxidation. The catalyst surface is able to re-oxidize in the stream of CO2 up to pristine level. Altogether, catalyst showed 78% H2 yield through dry reforming of methane.